Oxygenase Enzyme Activity and Compound Profile in Hydrocarbon Bioremediation by Pseudomonas aeruginosa and Rhodococcus erythropolis Consortium - Adi Tiya Yanuar; Abd. Aziz Amin; Lutfi Ni'matus Salamah; Frentina Murty Sujadi; Ekwan Nofa Wiratno; Citra Satrya Utama Dewi; Andi Kurniawan (Jurnal Ilmiah Perikanan dan Kelautan)
Abstract